A benefit-cost analysis approach for determining the optimal processing of micronutrient-enriched cowpea leaf soup mixes - Owade, Joshua Ombaka; Abong’, George Ooko; Okoth, Michael Wandayi; Mwang’ombe, Agnes Wakesho (Frontiers in Food Science and Technology, 2022)
Cost-effective techniques are usually recommended in the dissemination and adoption of postharvest processing technologies of food products. Due to limited value addition practices for cowpea leaf, the Fruits and Vegetables for All Seasons Project undertook a study to bridge the gap in the seasonal availability of the vegetable in the arid and semi-arid lands (ASALs) of Kenya through the production of cowpea leaf soup mix. However, the adoption of these techniques has an economic perspective that guides decision-making. This study utilized a two-stage linear programming methodology using NutriSurvey and the analytic hierarchy process in a seven-step hierarchy for the production of a cowpea leaf soup mix of an optimal nutrition and sensory quality. The optimal inclusion level of cowpea leaves into the soup mix was 49%. With an R2 of 61.36%, consistency, taste, and mouthfeel were the greatest determinants of the acceptability of cowpea leaf soup mixes. The incorporation of blanching in solar drying and sun drying were the least costly options with priority vectors of 0.08 and 0.09 (CR < 0.1) respectively, whereas, in the use of mechanized processing techniques such as oven drying, priority vectors of 0.10–0.19 had higher maximum benefits than the local processing technique of sun-drying that had a priority vector of 0.08 (CR < 0.1). The benefit-cost ratio was maximal without extrusion, with the solar-drying pathway having the highest benefit-cost ratio of 1.5. The study found that resource-intensive pathways yielded maximum benefits in the retention of quality. However, with the exclusion of extrusion, the benefit-cost ratio of the processes improved.